Influence of Arab Spring (2011) on Lebanon political life - Мырзaғұл, Ж Ұ. (Journal of Oriental Studies, 2017)
In the article is considered the impact of Arab Spring 2011 on the political life of Livan. It is analyzed the ethno-confessional system and the internal political situation in the country and the role of the party “Hezbollah”.